Embracing Responsible Leadership and Enhancing Organizational Citizenship Behavior for the Environment: A Social Identity Perspective - Xiao, Xiaohong; Zhou, Zheng; Yang, Fu; Qi, Huijie (Frontiers in Psychology, 2021)
Although organizational citizenship behavior for the environment (OCBE) literature has highlighted the critical role of leadership on the emergence of OCBE, there is still room for further research exploration of how and when leaders influence subordinates’ OCBE. According to social identity theory, we propose a theoretical model that responsible leadership promotes subordinates’ OCBE by examining subordinates’ moral identity as a mediator and individualism as a boundary condition. Using a sample of 273 collected in China, results indicated that responsible leadership was positively related to subordinates’ moral identity, which in turn was positively related to subordinates’ OCBE. Subordinates’ moral identity partially mediated the relationship between responsible leadership and their OCBE. In addition, both the relationship between responsible leadership and subordinates’ moral identity and the indirect relationship between responsible leadership and subordinates’ OCBE were stronger when individualism was lower. These findings provide novel insights into how responsible leadership influences OCBE and how such influence is shaped by subordinates’ individualism.